COMPARATIVE ANALYSIS OF CHEAP SINGLE-BOARD COMPUTER FOR OPTIMAL PERFORMANCE IN NINTENDO WII EMULATION (European Journal of Interdisciplinary Research and Development, 2023)
This research paper provides a comparative analysis of Single-Board Computers (SBCs) within a price range of $125 for optimal Nintendo Wii emulation performance. The objective is to identify the most suitable and cost-effective SBC capable of running Nintendo Wii games with high emulation performance and smooth action. Through installation, configuration, and testing using the Dolphin emulator on multiple platforms (Windows, Android, iOS, macOS, and Linux), it was determined that the Orange Pi5B with 4GB of memory provided the best performance, enabling smooth emulation of the majority of Nintendo Wii games. This research will aid vintage gaming enthusiasts and researchers in selecting a high-performance SBC for Nintendo Wii emulation within a reasonable budget.